ANALISIS POTENSI DAN STRATEGI PEMASARAN LOBSTER AIR TAWAR PADA KELOMPOK USAHA BERSAMA (KUB) SAN-JAYA DESA CINTA MAJU KECAMATAN SITIO-TIO KABUPATEN SAMOSIR PROVINSI SUMATERA UTARA - Dodianto, Dodianto (JURNAL CREATIVE AGUNG; Vol 14 No 2 (2024): OKTOBER, 2024)
This research was conducted to determine Marketing (Marketing Channel Patterns, Marketing Margins and Profits, Farmer'S Share, Marketing Efficiency) and Marketing Strategy (Enhancing and Inhibiting Factors) in marketing institutions in the research area. For data analysis using descriptive qualitative analysis. The results of the study concluded that the marketing channel or link for crayfish in the Study Area consisted of three marketing channels, the first KUB San-Jaya à Consumers, the second KUB San-Jaya à Intermediary Traders à Consumers and the third KUB San-Jaya à Collectors à Retailers à Consumers. Commodity Lobster Ait Tawara from fishing business in Lake Toba waters is based on location with an advantage of 1.47. First channel Farmer's Share 1.00; Second Channel 0.73 and Third Channel 0.44. Marketing Efficiency occurs in Channel One with a value of 2.00 percent. The Freshwater Lobster Marketing Development Strategy is in quadrant II or the Diversification Strategy, namely using strengths (formal registered legal aspects, potential natural resources and human resources) to minimize threats, namely: incidence of disease, polluted water and fluctuations in production costs .